Congenital Disorders of Autophagy: What a Pediatric Neurologist Should Know - Ebrahimi-Fakhari, Darius (Neuropediatrics, 2018)
Autophagy is a fundamental and conserved intracellular pathway that mediates the degradation of macromolecules and organelles in lysosomes. Proper autophagy function is important for central nervous system development and neuronal function. Over the last 5 years, several single gene disorders of the autophagy pathway have emerged: EPG5-associated Vici syndrome, WDR45-associated β-propeller protein-associated neurodegeneration, SNX14-associated autosomal-recessive spinocerebellar ataxia 20, ATG5-associated autosomal-recessive ataxia syndrome, SQSTM1/p62-associated childhood-onset neurodegeneration, and several forms of the hereditary spastic paraplegias. This novel and evolving group of disorders is characterized by prominent central nervous system involvement leading to brain malformations, developmental delay, intellectual disability, epilepsy, movement disorders, and neurodegeneration. Predominant involvement of the long white matter tracts and the cerebellum are anatomic and imaging hallmarks, with common findings that include a thinning of the corpus callosum and cerebellar hypoplasia or atrophy. A storage disease phenotype by clinical or imaging criteria is present in some diseases. Most congenital disorders of autophagy are progressive and over time involve pathology in multiple brain regions. This review provides a detailed clinical, imaging and genetic characterization of congenital disorders of autophagy and highlights the importance of this pathway for childhood-onset neurological diseases.
Keywords: autophagy; inborn errors of metabolism; mammalian target of rapamycin; lysosome; neurodevelopment; neurodegeneration